Moldable elastomeric polyester-carbon nanotube scaffolds for cardiac tissue engineering. (1st April 2017) - Ahadian, Samad; Davenport Huyer, Locke; Estili, Mehdi; Yee, Bess; Smith, Nathaniel; Xu, Zhensong; Sun, Yu; Radisic, Milica
Graphical abstract: Abstract: Polymer biomaterials are used to construct scaffolds in tissue engineering applications to assist in mechanical support, organization, and maturation of tissues. Given the flexibility, electrical conductance, and contractility of native cardiac tissues, it is desirable that polymeric scaffolds for cardiac tissue regeneration exhibit elasticity and high electrical conductivity. Herein, we developed a facile approach to introduce carbon nanotubes (CNTs) into poly(octamethylene maleate (anhydride) 1, 2, 4-butanetricarboxylate) (124 polymer), and developed an elastomeric scaffold for cardiac tissue engineering that provides electrical conductivity and structural integrity to 124 polymer. 124 polymer-CNT materials were developed by first dispersing CNTs in poly(ethylene glycol) dimethyl ether porogen and mixing with 124 prepolymer for molding into shapes and crosslinking under ultraviolet light. 124 polymers with 0.5% and 0.1% CNT content (wt) exhibited improved conductivity against pristine 124 polymer. With increasing the CNT content, surface moduli of hybrid polymers were increased, while their bulk moduli were decreased. Furthermore, increased swelling of hybrid 124 polymer-CNT materials was observed, suggesting their improved structural support in an aqueous environment. Finally, functional characterization of engineered cardiac tissues using the 124 polymer-CNT scaffolds demonstrated improved excitation threshold in materials with 0.5% CNT content (3.6 ± 0.8 V/cm) compared to materials with 0% (5.1 ± 0.8 V/cm) and 0.1% (5.0 ± 0.7 V/cm), suggesting greater tissue maturity. 124 polymer-CNT materials build on the advantages of 124 polymer elastomer to give a versatile biomaterial for cardiac tissue engineering applications. Statement of Significance: Achieving a high elasticity and a high conductivity in a single cardiac tissue engineering material remains a challenge. We report the use of CNTs in making electrically conductive and mechanically strong polymeric scaffolds in cardiac tissue regeneration. CNTs were incorporated in elastomeric polymers in a facile and reproducible approach. Polymer-CNT materials were able to construct complicated scaffold structures by injecting the prepolymer into a mold and crosslinking the prepolymer under ultraviolet light. CNTs enhanced electrical conductivity and structural support of elastomeric polymers. Hybrid polymeric scaffolds containing 0.5 wt% CNTs increased the maturation of cardiac tissues fabricated on them compared to pure polymeric scaffolds. The cardiac tissues on hybrid polymer-CNT scaffolds showed earlier beating than those on pure polymer scaffolds. In the future, fabricated polymer-CNT scaffolds could also be used to fabricate other electro-active tissues, such neural and skeletal muscle tissues. In the future, fabricated polymer-CNT scaffolds could also be used to fabricate other electro-active tissues, such as neural and skeletal muscle tissues.